2015
DOI: 10.1002/cne.23724
|View full text |Cite
|
Sign up to set email alerts
|

Feedback in the brainstem: An excitatory disynaptic pathway for control of whisking

Abstract: Sensorimotor processing relies on hierarchical neuronal circuits to mediate sensory-driven behaviors. In the mouse vibrissa system, trigeminal brainstem circuits are thought to mediate the first stage of vibrissa scanning control via sensory feedback that provides reflexive protraction in response to stimulation. However, these circuits are not well defined. Here, we describe a complete disynaptic sensory receptor-to-muscle circuit for positive feedback in vibrissa movement. We identified a novel region of tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 85 publications
(107 reference statements)
1
16
0
Order By: Relevance
“…In particular, both of these atlases show the dorsomedial nucleus extending farther ventrally than does Astrom (). Importantly, CGRP‐immunoreactive nerve fibers of the trigeminal nerve extend only into the dorsal region as defined by Astrom (Sugimoto et al, ; Matthews et al, ) and as shown in the present work. Moreover, it is only this dorsal region that shows citric acid‐induced c‐Fos.…”
Section: Discussionsupporting
confidence: 82%
“…In particular, both of these atlases show the dorsomedial nucleus extending farther ventrally than does Astrom (). Importantly, CGRP‐immunoreactive nerve fibers of the trigeminal nerve extend only into the dorsal region as defined by Astrom (Sugimoto et al, ; Matthews et al, ) and as shown in the present work. Moreover, it is only this dorsal region that shows citric acid‐induced c‐Fos.…”
Section: Discussionsupporting
confidence: 82%
“…7). Further, a projection from the muralis division of the trigeminal sensory complex to the facial nucleus has been reported (Matthews et al, 2015). This projection was proposed to be part of a reflex pathway.…”
Section: Discussionmentioning
confidence: 99%
“…8D). One possible explanation for how these signals may influence facial motoneurons, under current investigation, is that they act as commands that are relayed through trigeminal nuclei (Matthews et al 2015) that further project to facial motor neurons (Pinganaud et al 1999). It will be valuable to determine if similar neuronal coding applies to the cortical control of other orofacial actions (Sawczuk and Mosier 2001).…”
mentioning
confidence: 99%
“…One possibility is that rapid whisking is generated by a disynaptic feedback loop in the brainstem (Nguyen and Kleinfeld 2005; Deutsch et al 2012; Matthews et al 2015). That is, sensory signals generated by the motion of the vibrissa could drive the facial motoneurons, which in turn would regenerate a sensory signal, and so on.…”
mentioning
confidence: 99%